Hybrid Between PIECES Framework and Technology Acceptance Model (TAM) in Quality Testing Of Mobile Application Office Automation System (eKEMENKEU) - Ade Achmad Zulfahmi; Rifki Sadikin; Eni Heni Hermaliani (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Digital transformation is a necessity that must be carried out by the government that provides public services. The success of digital transformation is to innovate the Office Automation System Mobile Application System (eKemenkeu application) based on Android/IOS to support simplification of business processes so that they can be easily accessed via smartphone devices. To get feedback on the quality of the eKemenkeu application, testing was carried out using the PIECES Framework and by selecting the Technology Acceptance Model (TAM) variable, as well as the Smart PLS 3.0 tool. The study analyzed 100 respondent data using 7 hypotheses with the results of 2 accepted hypotheses, namely H1 Original Sample value (0.335) and t-statistics (2.864) and H7 Original Sample (0.748) and t-statistics (10.401), and the second significance level is above 0, 05. Meanwhile, 5 hypotheses were rejected, because the t-statistic value was > 1.96 and the significance level of the p-value was below 0.05. The results of the Discriminate Validity test ranged in value (0.786 - 0.949). Composite Reliability ranges in value (0.828 - 0.949) or is accepted because it is above 0.7. Cronbach's Alpha range of values (0.721-0.920) or satisfactory > 0.7 .